Proceedings of the International Conference of Early Childhood Education (ICECE 2017) 2018
DOI: 10.2991/icece-17.2018.7
|View full text |Cite
|
Sign up to set email alerts
|

Development of Moral and Religious Values for Children through Singing Themed Islamic Songs

Abstract: Abstract-The development of singing ability aims to make children able to create something based on their imagination. In addition, the development of singing ability can also sharpen the sensitivity and appreciate the creative work. Islamic songs are always close to the world of children and usually have started from the family environment because it is rich in moral messages. In digging the ability to sing a child can be used Demonstration Method. This is done by telling the song content and demonstrating it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Produk yang dikembangkan ini terbukti sangat layak untuk digunakan khususnya pada aspek agama dan moral AUD. Aspek moral dibentuk dari interaksi, training activities, dan respon lingkungan (Safitri, 2022;Septianti & Hafidz, 2021;Yeni, 2018). Media Big Book Prayer terbukti dapat meningkatkan interaktif antara guru dan anak menarik karena berbentuk media gambar besar yang berwarna warni, tidak membosankan, menyediakan lebih dari 1 aktifitas permainan.…”
Section: Pembahasanunclassified
“…Produk yang dikembangkan ini terbukti sangat layak untuk digunakan khususnya pada aspek agama dan moral AUD. Aspek moral dibentuk dari interaksi, training activities, dan respon lingkungan (Safitri, 2022;Septianti & Hafidz, 2021;Yeni, 2018). Media Big Book Prayer terbukti dapat meningkatkan interaktif antara guru dan anak menarik karena berbentuk media gambar besar yang berwarna warni, tidak membosankan, menyediakan lebih dari 1 aktifitas permainan.…”
Section: Pembahasanunclassified
“…From the seloko speech above, only one data contained religious values (see data 3). Religious values bind a person to God, religion, and beliefs that he believes (Rahima & Ridwan, 2016;Suryanto, 2016;Khuriyah et al, 2017;Yeni, 2018). Seloko speech in data 3 contained messages about obedience to existing laws in the Islamic religion and Malay tradition, which can serve as guidelines for life.…”
Section: Religious Valuesmentioning
confidence: 99%
“…However, Zamin et al (2020) found that the use of English songs from contemporary genres, such as Western or Islamic songs can be an effective way to promote language learning. Yeni (2018) remarks Islamic songs are the suitable song used in teaching vocabulary because it is rich in moral messages.…”
Section: Using Song In Eltmentioning
confidence: 99%